Learning Styles of Students With Intellectual Disabilities - Lisnawati, Devi; Tanya, Rafa; Salsabila, Putri Pathia; Fitriyani, Fitriyani (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
Mental retardation is a child with special needs who has below average intelligence, namely between 50-70. They experience obstacles in carrying out activities. anything, especially in learning (Sefni, 2014). Learning style is the preferred way of carrying out activities of thinking, processing and understanding information. The benefit o f this research is knowing the learning styles of mentally retarded children. Researchers conducted research with the aim of describing the learning styles of students with intellectual disability and knowing the difficulties of mentally retarded children in learning the material. The subjects of this research are mentally retarded children and teachers of mentally retarded children. The learning styles used by mentally retarded children are different. Some tend to be auditory and some tend to be visual depending on the type of mental retardation experienced. However, in determining the learning outcomes achieved by mentally retarded children through their learning styles, teachers experience a little difficulty. The intellectual abilities of mildly mentally retarded children are below average, making them experience learning difficulties and difficulties in receiving lessons, especially mathematics lessons. Teaching mathematics to children with mild mental retardation will be more successful if it uses something concrete, simple examples, language that is easy to understand, and is done in interesting and fun situations so that children with mild mental retardation do not get bored and are motivated to learn.